The managers' perception on importance of religiosity and corporate social responsibility in Malaysia / Nor Suziwana Tahir, Khaliq Ahmad and Noor Hazilah Abd Manaf - Tahir, Nor Suziwana; Ahmad, Khaliq; Abd Manaf, Noor Hazilah (Faculty of Administrative Science and Policy Studies, 2015)
Recently there have been major changes in the social expectation from the corporations and its managers. Many previous researches in Malaysia have deliberated on disclosing decent corporate practices and the effect of social and cultural differences. However, there is limited study on the importance of religiosity and Corporate Social Responsibility (CSR) on business practices especially the Public Listed Companies (PLCs). Therefore this study examines the managers' perception towards religiosity and CSR in the Malaysian context. The finding of this research discovers that managers perceived religiosity and CSR practices are an important part of business. The implication of this research on practitioners whereby they may use this findings to improve their decisions pertaining recruitment and selection and better understanding of CSR practices in Malaysian PLCs. This study only covers four industry and the questionnaires were distributed to middle management. While acknowledging several implications and limitations of this study, the significant findings would uncover many untold motives and this research will emulate future investigations on religiosity and CSR practices to make Malaysia's corporation a success.